Intermediary liability: evaluating the liability sections of section 53 (7) and (8) of Namibia's draft copyright and related rights bill 2021 - Ipinge, Ndapandula (Department of Commercial Law, 2025)
Internet intermediaries have enabled the general public to access information easier, including copyrighted work. This however led to right to right holders targeting intermediaries for copyright infringement instead identifying and suing every individual user of internet intermediaries. In order to reduce the liability risks for intermediaries, lawmakers around the world began to amend or adopt their law in particular through the introduction of exemption provisions. Case in point was the U.S The Digital Millennium Copyright Act which introduced safe harbour provisions under which intermediaries can escape liability. Similarly, the EU Electronic Commerce Directive of 2000 contains safe harbour provisions which limit the liability of intermediaries. In 2019, Namibia's Business Intellectual Property Authority (BIPA) began its journey of amending the Copyright and Neighbouring Rights Act order to be suitable for the digital era. After two consultations and reviews with stakeholder, the Draft Copyright and Related Rights Bill was published. Section 53 of the Bill expressly addresses the issue of internet service providers. The inclusion sections 53(7) and 53(8) raises concerns about increasing the liability of intermediaries considering their importance to the general public. This dissertation aims to consider if section 53(7) and (8) is constitute an appropriate liability regime.